THE USE OF SILENT WAY THROUGH DIGITAL FLASHCARDS: BENEFITS AND CHALLENGES - Muhamad Tegar Pratama PRATAMA; Isti Gandana (STKIP Siliwangi, 2024)
The 1970s marked the emergence of innovative pedagogical approaches, notably Caleb Gattegno's Silent Way, as a response to the shortcomings of traditional learning methods like the Grammar-translation approach, which persist today. This research investigates the advantages and challenges of implementing Silent Way at an English Club in Bandung. Two English teachers from the English Club comprised the study cohort, and a qualitative case study served as the chosen methodology. The researcher meticulously processed the analysis through multiple stages. The researcher closely examined the observations to capture detailed insights, while also condensing interview transcriptions for quick reference, contributing to a robust dataset. By combining data from both observations and interviews, this comprehensive approach guided the conclusions of the study, which were presented within the research framework. The findings underscore numerous benefits associated with the utilization of the Silent Way in teaching English to children within an English club. Particularly noteworthy is its capacity to heighten engagement, boost students' confidence, and enhance critical thinking skills. Nonetheless, the study identifies certain internal and external factors as impediments to the full-scale implementation of this teaching method.